Town design and town communications in the process of image creation of Wroclaw and Malaga - Waniowski, Paweł; Wojtaś, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Creating a positive image is one of the most important activities undertaken not only by enterprises, but also by territorial units. Cities and regions can see the need to create and maintain a good image as an important factor of competitive advantage facilitating opportunities for dynamic development. Nowadays, the most active in this respect are large urban centers which are managed in a creative way, and a good image, which is their most important intangible asset, definitely facilitates competition in increasingly demanding markets. The paper aims to present activities within town design and town communications, which, apart from town behavior, belong to the basic components of the process of creating the image of modern cities. One of the qualitative methods, which is a case study, was applied due to the possibility of making comprehensive comparisons based on the information identified. The examples of two culturally distant cities were used, namely the Polish city of Wroclaw and the Spanish city of Malaga, which, in many areas of creating their image, carry out similar activities. In both cities, the commercialization of city symbols is visible at the expense of historical and cultural aspects. The communication with stakeholders is similar, in which interactive techniques dominate, and particular activity manifests itself in social media and in the development of urban applications that perform both information and entertainment functions.
Keywords: city image; territorial marketing; Wroclaw; Malaga